Aktualne problemy edukacji uczniów z niepełnosprawnością w percepcji nauczycieli w różnych formach kształcenia specjalnego - Lipińska-Lokś, Jolanta (Wydział Studiów Edukacyjnych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2015)
Education of students with disabilities is a challenge for teachers engaged in various forms of special education. Due to recognizing the limitations and problems connected with education of such a diverse group of students, new solutions are sought.This article compares the higher education systems between China and Ukraine,
Current Problems of the Education of Students with Disabilities in The Perception of Teachers Engaged in Various Forms of Special Education System
Keywords: student with a disability; special education; special education teacher